Perancangan Model Prototipe Kehadiran Menggunakan Rfid Rc522 - Yuni Roza; Musliadi KH; Yonky Pernando (Scientific Literacy Innovation and Technology Journal, 2024)
In the era of increasing digitalization, the need for an efficient and accurate attendance system has become very important, especially in academic and professional environments. This research aims to design and develop a prototype presence model using RFID RC522 technology, which can provide an effective solution to various problems that exist in conventional presence systems such as data inaccuracy, presence manipulation, and inconvenience of use. The method used in this research includes hardware and software design. The hardware consists of an RC522 RFID module connected to an Arduino microcontroller, while the software was developed using the C++ programming language to manage communication between the RFID and the microcontroller, as well as storing attendance data in a database. Testing was carried out on a sample group of users to evaluate the accuracy and speed of the system in recording attendance. The research results show that the RC522 RFID-based presence system can identify and record user presence with a high level of accuracy and fast response time. This system has also proven to be more secure and difficult to manipulate compared to traditional presence methods such as manual signatures or identity cards without RFID technology. Additionally, users report increased convenience in the attendance recording process as it does not require direct physical contact with the device.